Examining the Influence of Principal Leadership on School Effectiveness : A Comprehensive Analysis in The Context of Primary Schools in Surabaya - Windasari, Windasari; Trihantoyo, Syunu; Roesminingsih, Erny; Vasodavan, Vinotini (Universitas Pendidikan Mandalika, 2024)
This study aims to analyze the influence of principal leadership on the effectiveness of primary schools. This research used a quantitative method. The research targets teachers in Surabaya, utilizing a sample of 376 respondents selected through a systematic random cluster sampling technique. The research instrument Principal Leadership adapted